IMPACT OF DRUG ABUSE AMONG STUDENTS IN GOMBE STATE COLLEGE OF EDUCATION: ADDRESSING YOUTH RESTIVENESS FOR NATIONAL DEVELOPMENT - Fatusi , Arike Omobolanle; Salau , Abiola Olanrewaju; Bwala , Suleiman James; Doka , Dacip Yerima (Int’l Journal of Education Research and Scientific Development, 2025)
This study is on the effects of drug abuse on students’ academic performance, health, and social relationships with a particular focus on science students at the Gombe State College of Education Billiri. Structured questionnaires were used to gather primary data through a simple random sampling technique. In total, 150 questionnaires were distributed and successfully retrieved for the study. The data collected were analyzed using basic averages and percentages. The respondents consisted of both males and females, aged between 15 and 40 years, and were students from various faculties within the college. Findings from the study showed that the majority of the respondents were females while most of the respondents fell in the age bracket 21-30. the most commonly used drugs among the students were alcohol, cannabis, and tramadol. The primary factors contributing to drug abuse among students are a lack of parental care, peer pressure, and poor relationships between teachers and students. The study further showed that over 70% of respondents felt that drug abuse affects their social lives, and a similar percentage agreed that it also has a negative impact on their academic performance.